Genomic identification of two Phytobacter diazotrophicus isolates from a neonatal intensive care unit in Singapore - Hon, Peiyun (2023)
We report the draft genome sequences of two Phytobacter diazotrophicus isolates recovered from a swab specimen from the water faucet located in the Neonatal Intensive Care Unit (ICU), National University Hospital, Singapore. The isolates were misidentified as Cronobacter sakazakii and Klebsiella oxytoca using biochemical methods. Whole-genome sequencing (WGS) was performed to determine their identity.